Respon Pertumbuhan Anggrek Dendrobium Terhadap Jenis Media Tanam dan Pupuk Daun - Andalasari, Tri Dewi; Yafisham, Yafisham; Nuraini, Nuraini (Jurnal Penelitian Pertanian Terapan, 2014)
The use of ferns as orchid growing media feel expensive, so it is necessary to find an alternative media as a media surrogate fern that has been used. This study aimed to explore alternative growing media and fertilizer is good for growth and development of dendrobium orchids. Selection of a good planting medium and the proper use of fertilizers can be expected to support healthy plant growth and quality of orchids. experiments were conducted at Greenhouse Faculty of Agriculture Lampung University. The experiment was conducted using a randomized design perfectly with the treatment group factorial (6x2). The first factor is the type of growing medium consists of wood charcoal (M1), fern (M2), husk + sawdust (M3), acacia bark (M4), cocochip (M5) and coconut bark (M6). The second factor is the type of foliar fertilizer consists of Gandasil (P1) and Hyponex (P2). Data were analyzed by analysis of variance followed by HSD test at 5% level. The results showed that the use of media orchids ferns produce good vegetative growth, no different to use of planting medium charcoal, charcoal husk + sawdust, bark and bark acacia tree coconut, but it is different than the use of cocochip shown in variable plant height, number of leaves , leaf length and leaf width. While fertilizers orchid leaves that produce good growth is fertilizer of Gandasil